Capital beats coal: How collecting the climate rent increases aggregate investment - Siegmeier, J; Mattauch, L; Edenhofer, O (Elsevier, 2017)
Carbon pricing is the key to decarbonizing the economy, as it regulates emission flows. However, a price on carbon also collects rents from underlying fossil resource stocks, giving rise to unexamined macroeconomic effects. This article shows that if these stocks are tradable, carbon pricing shifts aggregate investment towards alternative assets. If capital is underaccumulated, this implies lower costs of climate policy and a welfare improvement. We prove this beneficial investment shift from fossil stocks towards capital for the case of an emission trading scheme: specifically, we show that the higher the share of auctioned permits, the larger the beneficial investment effect. The same holds for a ‘stock instrument’, under which the right to recurrently receive emission permits is a tradable asset, making the effect robust to trade restrictions on fossil stocks. Our main result contradicts the common perception of a trade-off between climate change mitigation policy and growth.